IMPROVING CAROLUS SURABAYA HIGH SCHOOL STUDENTS' UNDERSTANDING OF THE ACCOUNTANT PROFESSION USING GAMIFICATION TEACHING METHODS - Magdalena, Renna; Risty, Ilyona; Herbert, Go George; Tjahjono, Josephine Kurniawati; Evangeline, Angela; Mandy, Mandy (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Lecturers and students from the Faculty of Economics and Business, Pelita Harapan University, carried out this service activity. Sharing knowledge and learning from each other has become the responsibility of people fortunate enough to receive higher education. Understanding the role of an accountant is very important for students who will later study at a university. This service is carried out using the concept of gamification. Gamification in learning is an approach that combines game elements into the learning context to increase student engagement, motivation, and understanding. This approach uses rewards, achievements, competitions, and challenges to spark interest and drive for learning. By implementing gamification in learning, high school students will understand the material better.